ASSESSMENT OF BRACKET BOND FAILURE DURING FIXED ORTHODONTIC TREATMENT BASED ON A QUESTIONNAIRE DISTRIBUTED TO ORTHODONTISTS - Manuela Nardin; Mihaela Ionescu; Diana-Elena Vlăduțu; Anne-Marie Rauten; Luminița Dăguci; Cristina Teodora Preoteasa; Alexandra Done; Veronica Mercuț (Romanian Journal of Oral Rehabilitation)
Introduction. The aim of this study was to evaluate the frequency of bracket bond failure and to identify the risk factors as well as the most frequently affected teeth. A secondary objective of the study was to establish whether white spot lesions (WSL), are frequently encountered during orthodontic treatment, while also quantifying their distribution at the level of the teeth. Materials and methods. The present research represents a cross-sectional study based on a questionnaire disseminated using the Google Forms platform between January and April 2024 and addressed exclusively to orthodontists in Romania. The data collected through the questionnaire was initially entered into a database in Microsoft Excel. Subsequently, statistical processing was performed using the Statistical Package for Social Sciences (SPSS) program, version 26 (IBM Corp., Armonk, NY, USA). Results. The questionnaire was completed by 113 orthodontists from different geographical areas of Romania. The majority of orthodontists reported 2 or 3 detached brackets at each orthodontic treatment (29.20% and 24.78%, respectively). Most frequently, orthodontists reported detachments from the level of several teeth (72.95%). Predisposed patients are male patients under 18 years of age during the first 6 months of treatment. Also, orthodontists observed that patients with Class II, division 2 anomalies had an increased likelihood of bracket detachment. According to the majority of respondents (67.26%), the posterior mandibular area is the most susceptible to bracket bond failures. The most common causes of bracket detachment were consumption of hard food and contact between the bracket and the opposite tooth, with 88.50% and 53.50% of orthodontists reporting these causes, respectively. Regarding the white spot lesions, 66.7% of orthodontists answered that these lesions appear mainly in the anterior maxillary area. Conclusions. Most of the detachments were reported at the level of the lower molars, the most frequently affected tooth being the first lower molar in quadrant IV. Potential risk factors for bracket detachment include age and gender of the patient, type of dento-maxillary anomaly, consumption of hard foods, contact between the bracket and the opposite tooth. As for the white spot lesions, they are associated with orthodontic treatment and appear mainly in the anterior maxillary area.